Resource Allocation In Energy Sustainable Wireless Mesh Networks - Sayegh, Amir Antoun Renne (My University, 2008)
Wireless LAN (WLAN) mesh networks are now being used to deploy Wi-Fi coverage in a wide variety of outdoor applications. In these types of networks, conventional WLAN mesh nodes must be operated using continuous electrical power connections. This requirement may often be very expensive, especially when the network includes expansive outdoor wireless coverage areas. An alternative is to operate some of the WLAN mesh nodes using an energy sustainable source such as solar or wind power. This eliminates the need for a fixed power connection, making the node truly tether-less and allowing for more flexibility in node positioning. The cost of the battery and the solar panel or wind turbine can be a significant fraction of the total node cost, therefore the resource allocation must be performed optimally.
In this thesis we investigate this problem. First, we present geographic provisioning results for solar and wind powered WLAN mesh nodes. The results suggest that in certain geographic locations a hybrid wind/solar powered WLAN mesh node is the optimum minimum cost configuration. The results also provide strong motivation for introducing power saving to the IEEE 802.11 standard. We then consider the problem of cost-optimal node placement in a hybrid network containing traditional and energy sustainable nodes. Our results show that there is a significant improvement in cost that can be obtained using the proposed methodology. Finally, we consider the problem of energy management in these networks. A control algorithm is proposed that uses access to publicly available meteorological databases. We show that the proposed algorithm minimizes node outage and performs favorably compared to the analytic performance bounds. Overall, the work in this thesis develops analytical and simulation models which investigate the key aspects pertaining to resource allocation in energy sustainable WLAN mesh networks.
Keywords: Wireless LAN; Wi-Fi; outdoor applications; sustainable energy; wind power; solar power